Effect of Clove essential oil (Syzygium aromaticum) against the growth of dandruff scalps-causing fungal pathogen using Kirby- Bauer method in vitro - Khusnul Khusnul; Puput Putuh Anisa; Dewi Peti Virgianti (Journal of Microbial Systematics and Biotechnology, 2021)
One of the strongest contributing factors in dandruff scalps is the presence of fungal pathogen or called as Malassezia. Several studies have found a connection between Malassezia and scalp health, one of which is caused by pathogenic fungal infections including Pityrosporum ovale, Microsporum gypseum, and Candida albicans. Clove flowers are known to contain eugenol and its derivative compounds which have antimicrobial, antifungal, antiseptic, and local anesthetic activity. This research aims to determine the effect of clove flower essential oil (Syzygium aromaticum) against some dandruff-causing fungi. The research method was to test the inhibitory power of clove flower essential oil using the diffusion method (Kirby Bauer technique). Samples of pathogenic fungi were cultured on SDA media (Saboroud Dextrose Agar) and given discs that had been given several concentrations of clove flower essential oil. The concentrations used were 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90%, 100%, positive control using 2% ketoconazole and negative control using virgin coconut oil (VCO). The results showed a significant effect between the ability of essential oils to inhibit the growth of some fungi that cause dandruff. The treatment of clove flower essential oil against M. gypseum at the concentration of 10% has an inhibitory ability of 33,05 mm and at the concentration of 100% amounted to 63.95 mm. Meanwhile, the inhibition percentage in P. ovale with a concentration of 10% and 100% of extract were 14,75 mm and 46,15 mm, respectively. The inhibition rate in C. albicans with the concentration of 10% extract and 100% of extract was 13,5 mm and 39,35 mm. The research shows that clove flower essential oil inhibits the growth of several pathogenic fungal in vitro.